2010
DOI: 10.1111/j.1553-2712.2010.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Difficulty Achieving Initial Control With Crotalidae Polyvalent Immune Fab Antivenom in Snakebite Patients

Abstract: Background: The prescribing information for Crotalidae Fab antivenom (FabAV) instructs clinicians to administer FabAV until initial control of the envenomation syndrome is achieved. Risk factors for difficulty achieving initial control are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…However, initial control was not achieved after 2 doses, and the patient required repeated doses over a 12-day span, which is among the longest durations of antivenom therapy described. Neurologic deficits and thrombocytopenia prior to administration of antivenom are independently associated with failure to achieve initial control, both of which occurred in this patient [7]. The recurrence phenomenon and unique clinical aspects of this case may have also contributed to the protracted course.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, initial control was not achieved after 2 doses, and the patient required repeated doses over a 12-day span, which is among the longest durations of antivenom therapy described. Neurologic deficits and thrombocytopenia prior to administration of antivenom are independently associated with failure to achieve initial control, both of which occurred in this patient [7]. The recurrence phenomenon and unique clinical aspects of this case may have also contributed to the protracted course.…”
Section: Discussionmentioning
confidence: 82%
“…One required 46 vials; however the clinical details of the case are not described [7]. The other describes a 50-year-old man also bitten by a 6-foot Eastern Diamondback rattlesnake requiring 51 total vials of antivenom with the last 6 vials given as continuous intravenous infusion over 36 hours to dissipate the recurrent coagulopathy on day 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The safety of FabAV was subsequently established, and observational studies demonstrated that FabAV administration is associated with cessation of progression of tissue injury in copperhead victims. 8,13,14 Whether this leads to improved recovery of limb function is unstudied, and the role of FabAV in the management of patients with nonlife-threatening envenomation is controversial. Although many experts recommend treating all crotaline envenomation patients according to clinical presentation, irrespective of species, others recommend withholding FabAV from copperhead victims.…”
Section: How This Is Relevant To Clinical Practicementioning
confidence: 99%
“…[3][4][5] More than 95% of copperhead victims develop significant pain and swelling of the envenomated limb, but systemic venom effects are uncommon and death is rare. [6][7][8][9] Current data support only a crude understanding of the time course of recovery from limb injury with or without antivenom therapy. Although most patients …”
Section: Introduction Backgroundmentioning
confidence: 99%